Cultural Diplomacy in Salman Rushdie’s Shalimar the Clown - Chandra Bahadur K. C. (Interdisciplinary Journal of Management and Social Sciences, 2022)
Cultural diplomacy refers to the relationships between two or more countries through the exchanges of cultural activities. Its key principle is to foster common values like faith, social justice, and responsibility. Cultural diplomacy helps people from diverse backgrounds to find common ground. A literary text like a novel can express the issues of identity and culture that are relevant to the readers of different nations and cultures. The purpose of this article is to give the theoretical concept of cultural diplomacy and to dig out the ingredients of cultural diplomacy inherent in Salman Rushdie’s novel Shalimar the Clown. This paper asserts that the novel is a great literary work to study cultural diplomacy. The novel tries to justify that the external selfish interference can change a paradise-like place into a battleground butchering human beings in a very inhuman way. The novel presents Kashmir as a melting pot for all religious followers before it was intruded on by outsiders. The misuse of power by a diplomat like Max Ophuls, an American ambassador to India, causes great misfortunes in his own as well as the lives of many others. As the result of the selfish interests of the foreign countries, Kashmir becomes a battleground with mass killings, genocides, frequent rape cases, and mass exodus. This type of realistic depiction of Southeast Asia, mainly Kashmir, in the novel shows how the selfish desires of different nations create situations of chaos. The ideas that the novel uses to describe Southeast Asia, mainly Kashmir, help readers make up their minds about that area. The readers may long for harmonious relations between different nations. It happens mainly because of the literary artifact i.e. the novel that expresses cultural diplomacy. The fictional characters and the fictitious societies depicted in the novel help us understand foreign countries and foreign cultures. The reader certainly takes the novel as a work that advocates cultural harmony